One-Step Hydrothermal Strategy for Preparation of a Self-Cleaning TiO2/SiO2 Fiber Membrane toward Oil-Water Separation in a Complex Environment - Yinghao Lin; Atian Xie; Jian Xu; Changguo Xue; Jiuyun Cui; Jianming Pan (Membranes, 2023)
Oil pollution caused by a large number of industrial activities and oil spill accidents has posed serious harm to the environment and human health. However, some challenges remain with the existing separation materials, such as poor stability and fouling resistance. Herein, a TiO2/SiO2 fiber membrane (TSFM) was prepared by a one-step hydrothermal method for oil-water separation in acid, alkali, and salt environments. The TiO2 nanoparticles were successfully grown on the fiber surface, endowing the membrane with superhydrophilicity/underwater superoleophobicity. The as-prepared TSFM exhibits high separation efficiency (above 98%) and separation fluxes (3016.38–3263.45 L·m−2·h−1) for various oil-water mixtures. Importantly, the membrane shows good corrosion resistance in acid, alkaline, and salt solutions and still maintains underwater superoleophobicity and high separation performance. The TSFM displays good performance after repeated separation, demonstrating its excellent antifouling ability. Importantly, the pollutants on the membrane surface can be effectively degraded under light radiation to restore its underwater superoleophobicity, showing the unique self-cleaning ability of the membrane. In view of its good self-cleaning ability and environmental stability, the membrane can be used for wastewater treatment and oil spill recovery and has a broad application prospect in water treatment in complex environments.